2022
DOI: 10.1001/jamanetworkopen.2022.14514
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Medical Oncologists and a Machine Learning Model to Predict 3-Month Mortality in Patients With Metastatic Solid Tumors

Abstract: Key Points Question How do oncologists and a machine learning model compare in predicting 3-month mortality for patients with advanced solid tumors? Findings In this prognostic study, the machine learning model significantly outperformed 74 oncologists in predicting 3-month mortality for 2041 patients with metastatic solid tumors overall and in gastrointestinal and breast cancer subpopulations. Findings were not significant in genitourinary, lung, and rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Study 3. In a study published by Zachariah and colleagues, 24 the positive likelihood ratios (PLRs) support the conclusion drawn by the authors that the machine learning (ML) model outperforms the oncologists at utilizing the surprise question to predict the patients with a higher 3-month mortality (Table 3). Of great significance however, calculation of the NLRs suggest that negative or "yes" responses to both SQ and ML model are not an effective method to screen for 3-month mortality estimation.…”
Section: Receiver Operating Characteristics Curvesmentioning
confidence: 63%
“…Study 3. In a study published by Zachariah and colleagues, 24 the positive likelihood ratios (PLRs) support the conclusion drawn by the authors that the machine learning (ML) model outperforms the oncologists at utilizing the surprise question to predict the patients with a higher 3-month mortality (Table 3). Of great significance however, calculation of the NLRs suggest that negative or "yes" responses to both SQ and ML model are not an effective method to screen for 3-month mortality estimation.…”
Section: Receiver Operating Characteristics Curvesmentioning
confidence: 63%
“…The integration of mortality risk into clinical practice remains a subject of ongoing investigation. Several academic hospitals have recently published promising workflows and initiatives to enhance serious illness conversations, 35 , 36 , 37 , 38 including a recent study of 20 506 oncology patients using a machine-learning algorithm to generate prompts, which successfully increased serious illness conversations from 3.4% to 13.5% and decreased end-of-life systemic therapy. 39 In these studies, multiple barriers have been identified, including lack of clinician engagement, alert fatigue, restricted or biased prediction models, and limited practice capacity for serious illness conversations.…”
Section: Discussionmentioning
confidence: 99%
“…Zachariah, Rossi, Roberts, and Bosserman (2022) used a ML model based on artificial neural networks (ANN) to compare the treatment suggestions made by medical oncologists and the AI algorithm. The ANN was trained on a data set of breast cancer patients, and the algorithm was able to suggest treatments that were similar to those suggested by the oncologists.…”
Section: Adoption Of Machine Learning In the Health Sectormentioning
confidence: 99%